UJI COBA PENGOLAHAN AIR WADUK MENJADI AIR MINUM DENGAN METODA KOAGULASI FILTRASI, DAN KLORINASI - Endiqaputri Dwi Damayanti; Suroso Bambang Eko Warno; Suprijandani . (GEMA LINGKUNGAN KESEHATAN, 2016)
Human needs water to meet the main needs for drinking water. In some areas in Indonesia, especially Dusun Karangwungu, Gresik shortage of water still frequently happens. The absence of water treatment in the reservoir exists in the area prompted me to conduct a research on physical, chemical, and microbiology of the water to be processed as drinking water. This is a descriptive typed study and data were collected through the use of secondary data, laboratory examinations, and observations. After sampling, the sample was then given the treatment of coagulation, fitasion and chlorination. Laboratory results were then compared with Minister Regulation No. 492 of 2010. The objective of this study was to proceed the reservoir water into drinking water in accordance with the Minister of Health Regulation number 492 year 2010 on Drinking Water Quality. The results of the study showed reduction in 19 test parameters in accordance with Permenkes 492/2010. The results showed that the reservoir water can be used as raw material for drinking water by coagulation, filtration, and chlorination. To society is expected to use reservoir water into drinking water to meet the needs. Further research for additional parameters in accordance with the Health Minister Regulation 492/2010 and Breakpoint chlorination and Chlor absorbance Power in chlorination process can be carried out. Keywords : coagulation, filtration, chlorination of drinking water